Acute Carbamazepine Toxicity: ACase of Rare Drug Interaction - N, Loganathan; S, Sujithkumar; K, Bhuvaneswari; V K, Thiagarajan (Indian Journal of Pharmacy Practice)
Carbamazepine is used in the treatment of simple partial, complex partial and in generalized tonic clonic seizures. It is also used in the treatment of trigeminal neuralgia and in manic depressive illness. Erythromycin is a macrolide antibiotic often used in infections like mycoplasma, legionella infections and other infections caused by aerobic gram positive cocci and bacilli. It is also used in diabetic gastro paresis and in those with an allergy to penicillin. Pharmacokinetic studies have established that erythromycin causes carbamazepine toxicity when these two drugs are given concurrently. One needs to be aware that this drug combination predictably causes adverse side effects hence, alternative antibiotic therapy should be considered for patients receiving long-term carbamazepine therapy who need antibiotic coverage. We report a case of carbamazepine toxicity induced by the concurrent administration of erythromycin.
Keywords: Carbamazepine; erythromycin; ataxia